Phenotypic diversity analysis of iron rich rice landraces (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Anemia in human being due to iron deficiency would be solved with the intake of iron rich rice (Oryza sativa L.) grain developed by biofortification. Phenotypical study of obsolete rice germplasms containing high iron content is important. Phenotypic characters like flowering and maturity time; plant height; tillers hill‑1; grains panicle‑1; seed weight and grain yield plant‑1 were studied for 39 rice genotypes in this research. In this research, Malagoti showed early maturity (126 day), Dhar Shail showed highest  filled grain panicle-1 (303), Marish Shail showed highest grain yield plant-1 (86.66g),  and Karengal showed lowest  filled grain panicle-1 (59.67) and lowest  grain yield plant-1 (17.20g). Number of filled grains panicle-1 showed high heritability. All the yield contributing traits except panicle length and unfilled grains panicle-1 were significantly and positively correlated with grain yield plant-1 at both phenotypic and genotypic level. The highest direct effects (0.486 and 9.75) on grain yield plant-1 were found for plant height and days to maturity at phenotypic and genotypic level with residual effect 0.461 and 0.496 respectively. Finally, the obsolete genotypes with highest grain yield (Marish Shail) and early maturity (Malagoti)  performance would be used as breeding materials to improve iron rich rice varieties.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 15-22